PHILOSOPHY OF 20-30 YEARS OF XX CENTURY IN AZERBAIJAN AS AN IDEOLOGICAL FACTOR - MUSAEVA, V.K (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
In the 1920s and 1930s, it was believed in the USSR that only communism can create and appreciate real art, and that only in a socialist society such an aspect can express its social potential and the power of belonging to the people. The country's leadership, using the possibilities of political power, tried not to violate the general ideological line and fought with opponents. Under the strict control of party leaders, the new "socialist" style is applied in the fields of architecture, applied arts, painting and music, literature and art with the aim of suppressing the "bourgeois" style. When assessing the past, when analyzing the problems of our time, any work or article that went beyond the framework of political ideology was rejected, and the author was subjected to political persecution. The leadership instructed to reject nihilism and ensure that works in the field of art and science are consistent with contemporary topics and requirements, as well as the requirements of ideology. The main idea of the policy pursued here was that "the highest forms of culture" should belong to the people, and the elitist approach of the past should be ended. Cultural reforms have created another problem. Some local authorities tried to artificially subordinate cultural activities to industrial and agricultural production. At the same time, they tried to instill in the training of specialists purely practical, utilitarian qualities and skills, to give a minimum of technical knowledge. As a result, general cultural development, political literacy were not taken into account, the social and political responsibility of the proletariat was lost and common (and technical) goals were lost.